Chach. (Finds Of the Objects with Christian Symbols) - Musakaeva A.A. (Zien Journals, 2021)
The article publishes subjects related to Christian culture. There are published unique finds of objects from Chacha of the period of antiquity and the early Middle Ages.
Keywords: coin; money; turnover; coinage